Chemical and pharmacological evaluation of Manglicolous lichen Graphis ajarekarii PATW. & C. R. KULK. - Haritha, Polimati; Patnaik, Sunil Kumar; Tatipamula, Vinay Bharadwaj (Vietnam Journal of Science and Technology, 2019)
The chemical examination of ethanolic extract of manglicolous lichen Graphis ajarekarii (Ga-Et) resulted in isolation of three known metabolites – chiodectonic acid (1), graphenone (2) and graphisquinone (3). All the isolates (1-3) and Ga-Et were screened against DPPH and superoxide free radicals, six different cancer cell lines and one normal human cell line (NHME). This work is the first report of antioxidant and cytotoxicity studies on the isolated metabolites (1-3).